Revisiting the late Quaternary fossiliferous infills of Cathedral Cave, Wellington Caves (central eastern New South Wales, Australia) - Diana A. Fusco; Lee J. Arnold; Grant A. Gully; Vladimir A. Levchenko; Geraldine E. Jacobsen; Gavin J. Prideaux (Journal of Quaternary Science, 2023)
The Wellington Caves were the first Australian locality from which Europeans collected and analysed vertebrate fossils. Within this system, Cathedral Cave contains Australia's stratigraphically deepest sequence of fossil‐bearing infill sediments, the age and depositional history of which has been poorly understood. Here we present results from a new excavation of the upper 4.2 m of the deposit, reanalysing the stratigraphy, petrography, sedimentology and geochemistry, and employing optically stimulated luminescence dating, radiocarbon dating and Bayesian age modelling to establish a robust chronology. We recognise 13 sedimentary layers and sublayers in two stratigraphic units. Unit 2 accumulated between 72 000 ± 5000 and 38 000 ± 7000 years ago as sediments and animals entered through a now‐blocked ceiling hole. Accumulation halted for around 30 000 years when the hole closed. Unit 1 accumulated when deposition was reinitiated around 7000 ± 2000 years ago, continuing through to a few hundred years ago. Our chronology refutes earlier dating of the deposit, which suggested that extinct Pleistocene megafauna taxa persisted locally until the Last Glacial Maximum. It confirms the deposit as one of the few in Australia that formed during the interval of major environmental upheaval marked by the arrival of humans, variable climate and the extinction of many megafaunal species.